About the prerequisites for the emergence of anatomy in ancient Greece. - Gurkin, V. A. (Морфологія / Morphologia / Morfologìâ, 2018)
The article is devoted to the analysis of the situation of the appearance of the first anatomical studies of animals in the science of Ancient Greece. The work of natural philosophers: Alcmaeon of Croton, Empedocles and Diogenes Apollonius on the relationship between the respiratory and circulatory systems of animals, as well as their relationship with the provisions of the Pythagorean philosophical doctrine is considered.